Characteristics of The Three Cultivar Physiological Growth of Jatropha curcass L. in Two Different Locations Based on Topography - Kovertina Rakhmi Indriana; Cucu Suherman; Santi Rosniawaty; Sumadi Sumadi; Dodi Sukmayana (Bogor Agricultural University, Indonesia, 2021)
The purpose of this study was to reveal the sensitivity of cross-location based on topography by giving different FMA consortiums to physiological growth characteristics in three Jatropha curcass L. cultivars. Based on these objectives, the nature of this research is verification. Experiments were carried out in two different places based on topography. The trial time starts from November 2017 to May 2018. Experiments A simple randomized block design (RBD) pattern consisting of fifteen treatment combinations is repeated twice. The experimental results showed that the dose of 10 gr FMA consortium (glomus sp., Acaulospora sp., Gigaspora sp.). With the same spore density gave the best performance of Jatropha plant growth in two different locations based on topography. Observation of chlorophyll content in leaves (age 21, 63, 21 DAP in two locations), plant height (age 21, 63, 21 DAP in two locations), stem diameter (age 21, 63, 21 DAP in two locations) and number of branches secondary (age 21 DAP in two locations) there was a significant effect on the single factor of giving the FMA consortium but there was no interaction between location and treatment.